1987
DOI: 10.3382/ps.0660480
|View full text |Cite
|
Sign up to set email alerts
|

Production Performance of White Leghorn Layers Fed Lactobacillus Fermentation Products

Abstract: A series of trials was conducted to determine if adding a Lactobacillus fermentation product (LAC) to the feed of laying hens would improve their production performance. Feeding a liquid, nonviable LAC product to either cage or floor housed laying hens did not improve hen-day egg production, feed efficiency, nor egg size during a 48 week experimental period. Laying hens fed a dried, nonviable LAC product did not show any improvement in hen-day egg production nor feed efficiency compared with laying hens fed no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 4 publications
2
7
0
1
Order By: Relevance
“…Laying rate did not differ amongst hens that received the control, Prob-1 and Prob-3 treatments. These findings are consistent with the results of preliminary laying hen trials that have reported that probiotic dietary supplements have either some (Krueger et al, 1977;Miles et al, 1981;Nahashon et al, 1994b;Mohan et al, 1995;Yörük et al, 2004) or no beneficial effects (Cerniglia et al, 1983;Goodling et al, 1987;Nahashon et al, 1994c;1996a,b). Settable egg production followed the same trend as that observed in hen-day egg production rates (Table 7).…”
Section: Broiler Breederssupporting
confidence: 81%
See 3 more Smart Citations
“…Laying rate did not differ amongst hens that received the control, Prob-1 and Prob-3 treatments. These findings are consistent with the results of preliminary laying hen trials that have reported that probiotic dietary supplements have either some (Krueger et al, 1977;Miles et al, 1981;Nahashon et al, 1994b;Mohan et al, 1995;Yörük et al, 2004) or no beneficial effects (Cerniglia et al, 1983;Goodling et al, 1987;Nahashon et al, 1994c;1996a,b). Settable egg production followed the same trend as that observed in hen-day egg production rates (Table 7).…”
Section: Broiler Breederssupporting
confidence: 81%
“…No significant differences in feed consumption between Prob-2 and Prob-3 treatments, and also between Prob-1 and control treatments, were determined (P>0.05). In full agreement with our findings, Balevi et al (2001) have indicated that feed consumption for brown layers fed a probiotic (Protexin)-added diet was 2.69 g lower than that of hens given a control diet, while others have reported that probiotic feeding has no significant effects (Cerniglia et al, 1983;Goodling et al, 1987;Nahashon et al, 1994cNahashon et al, , 1996a. Based on the results of the present and previous studies, the influences of dietary probiotics on feed intake could be said to be variable, but no deleterious effect on performance was observed in this case.…”
Section: Laying Henssupporting
confidence: 81%
See 2 more Smart Citations
“…Several studies with layers indicated that supplementation of probiotics increases the egg production and feed conversion 5, 8, 9. However, a number of studies have shown that probiotics have no positive effects on layers' performance 10, 11. Variation in the effects of probiotics obtained from various studies has been attributed to the difference in the strains,12 form of bacteria,13 their concentrations in the diet4 and viability in the gastrointestinal tract 10…”
Section: Introductionmentioning
confidence: 99%